This is My Baby Interview: an adaptation to the spanish language and culture - Benítez-Lugo, Marisa; Sánchez González, María Carmen; Pinero‐Pinto, Elena; Palomo‐Carrión, Rocío; Romero-Galisteo, Rita Pilar (My University, 2022)
INTRODUCTION: Evaluating the emotional state of the parents is important for determining the intervention in the context of a family with a baby with Down syndrome. "This is my baby" is an interview that measures the acceptance, commitment and awareness of influence of parents towards their baby. The Spanish adaptation of this instrument helps to better understand the emotional state of parents of children with developmental disorders. PATIENTS AND METHODS: This is a transcultural adaptation and determination of the reliability, sensitivity to change, and internal consistency of the “This Is My Baby” interview. A cross-cultural adaptation and reliability analysis was carried out. A total of 32 families of babies with Down syndrome participated in this multicenter study. RESULTS: The values obtained for the intraclass correlation coefficient (ICC) indicated a good level of concordance with a significative level of p < 0.001, and the values of the standard error of measurement (SEM) and of the minimum detectable change (MDC) were reduced. The weighted Kappa coefficient showed values that were moderate to excellent. CONCLUSION: The results suggest that the Spanish version of the This Is My Baby interview is a reliable instrument to measure the levels of acceptance, commitment, and awareness of influence of parents of an infant with Down syndrome.
Keywords: Emociones; Pediatría - Investigación; Down, Síndrome de; Psicometría; Pediatría